Boosting Electrochemical Activity of Porous Transparent Conductive Oxides Electrodes Prepared by Sequential Infiltration Synthesis. Issue 12 (20th February 2022) - Ko, Minkyung; Kim, Hyeong‐U; Jeon, Nari
Abstract: Sequential infiltration synthesis (SIS) is an emerging technique for producing inorganic–organic hybrid materials and templated inorganic nanomaterials. The application space for SIS is expanding rapidly in areas such as lithography, filtration, photovoltaics, antireflection, and triboelectricity, but not in the field of electrochemistry. This study performs SIS for the fabrication of porous, transparent, and electrically conductive films of indium zinc oxide (IZO) to evaluate their potential as an electrode for electrochemistry. The electrochemical activity of IZO‐coated electrodes is evaluated when their surfaces are modified with ferrocenecarboxylic acid (FcCOOH), a model redox molecule. Results show a 25‐fold enhancement in peak current densities mediated by an Fc/Fc + redox couple for an IZO‐coated electrode in comparison with bare electrodes; this is afforded by the porous morphology of the IZO film and the enhanced binding efficiency of FcCOOH on the IZO film. The results confirm the potential of SIS for the preparation of porous transparent conducting oxide electrodes, which will enable the application of SIS‐derived materials in various electrochemical fields. Abstract : Sequential infiltration synthesis is performed for the fabrication of porous, transparent, and electrically conductive films of indium zinc oxide (IZO). The significant enhancement of the electrochemical activity of the IZO‐coated electrodes is afforded by the porous morphology of the IZO film and the enhanced binding efficiency of a model redox molecule, ferrocenecarboxylic acid, on the IZO film.